2021
DOI: 10.3389/fmed.2021.663608
|View full text |Cite
|
Sign up to set email alerts
|

Scoring System to Evaluate the Performance of ICU Ventilators in the Pandemic of COVID-19: A Lung Model Study

Abstract: Ventilators in the intensive care units (ICU) are life-support devices that help physicians to gain additional time to cure the patients. The aim of the study was to establish a scoring system to evaluate the ventilator performance in the context of COVID-19. The scoring system was established by weighting the ventilator performance on five different aspects: the stability of pressurization, response to leaks alteration, performance of reaction, volume delivery, and accuracy in oxygen delivery. The weighting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In severe restrictive pulmonary mechanics scenarios (i.e., COVID-19), the performance of COVIDair regarding inspiratory trigger sensitivity remains the same. With optimal setting, the inspiratory TDT was always less than 100 ms. A scoring system has been proposed to evaluate the performance of ICU ventilators in the context of the COVID-19 pandemic [ 6 ]. Even though the investigation was carried out slightly differently in the present study, the performance of the COVID air demonstrated values of inspiratory TDT (86.4 (±2.9) ms) close to the targeted best value (i.e., maximal score in the scoring system) of 60.0 ms in low compliance plus increased respiratory effort COVID-19 scenario (i.e., compliance 20 mL/cmH 2 O, respiratory rate 40 cycles/min and inspiratory effort of 10 cmH 2 O).…”
Section: Discussionmentioning
confidence: 99%
“…In severe restrictive pulmonary mechanics scenarios (i.e., COVID-19), the performance of COVIDair regarding inspiratory trigger sensitivity remains the same. With optimal setting, the inspiratory TDT was always less than 100 ms. A scoring system has been proposed to evaluate the performance of ICU ventilators in the context of the COVID-19 pandemic [ 6 ]. Even though the investigation was carried out slightly differently in the present study, the performance of the COVID air demonstrated values of inspiratory TDT (86.4 (±2.9) ms) close to the targeted best value (i.e., maximal score in the scoring system) of 60.0 ms in low compliance plus increased respiratory effort COVID-19 scenario (i.e., compliance 20 mL/cmH 2 O, respiratory rate 40 cycles/min and inspiratory effort of 10 cmH 2 O).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mechanical ventilator is applied to patients with acute or acute-on-chronic respiratory failure that do not respond to standard therapeutic interventions, such as antibiotics, bronchodilators, etc. [ 28 , 29 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%